1988
DOI: 10.1007/bf00303033
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible compartmentalization of individual chromosome domains in human CNS cells revealed by in situ hybridization and three-dimensional reconstruction

Abstract: Specific chromosome domains in interphase nuclei of neurons and glia were studied by three-dimensional (3-D) reconstruction of serial optical sections from in situ hybridized human CNS tissue. Overall patterns of centromere organization, delineated with alphoid repeats, were comparable to those seen in mouse, and are clearly conserved in mammalian evolution. Cloned probes from other individual chromosome domains were used to define interphase organization more precisely. Homologous chromosomes were spatially s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(151 citation statements)
references
References 47 publications
9
142
0
Order By: Relevance
“…This molecular segregation of LINE and SINE motifs into structurally distinct compartments has recently been confirmed (30). In extended interphase chromosomes, LINE repeats are detected as -250 nm wide spots of varying length (46,47). From the structural model above it can be predicted that linear DNAs of 300 kb to >1.5Mb should contain clusters of LINE sequences.…”
Section: Bands and Subbandsmentioning
confidence: 69%
See 1 more Smart Citation
“…This molecular segregation of LINE and SINE motifs into structurally distinct compartments has recently been confirmed (30). In extended interphase chromosomes, LINE repeats are detected as -250 nm wide spots of varying length (46,47). From the structural model above it can be predicted that linear DNAs of 300 kb to >1.5Mb should contain clusters of LINE sequences.…”
Section: Bands and Subbandsmentioning
confidence: 69%
“…In contrast, early repli- Urd-peroxidase labeled) in prometaphase spread. Open arrow points to labeled fine domain a t 1~36.3, likely to be the site of a minisatellite (47); the surrounding extended early replicating regions that are unlabeled have previously been shown to contain a high concentration of GC rich SINES (46). The length of chromosome 1 in this prometaphase preparation (that is not maximally extended) is 10 Fm.…”
Section: Bands and Subbandsmentioning
confidence: 90%
“…Several lines of evidence suggest that the perinucleolar compartment functions as a repressive environment in other cell types. Nucleoli in higher eukaryotes are surrounded by a layer of heterochromatin (1,4,5,(48)(49)(50). In mammalian ES cell cultures, the inactive X chromosome (Xi) or autosomes expressing the Xist transcript visit the perinucleolar space in S phase (9).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, centromeric and other highly repeated nontranscribed sequence domains may be positioned on the nucleolus or nuclear membrane and act as general organizing centers for cell type-specific interphase patterns (21). Multiple adjacent replicons appear to be clustered on fixed sites of the nuclear matrix (17,271, and it has been suggested that clustered replication origins are activated simultaneously (25).…”
mentioning
confidence: 99%